Reformed Christology: Historical Foundations and Contemporary Doctrinal Implications - Basri, Herman Adi; Panggarra, Robi (Sekolah Tinggi Teologi Simpson Ungaran, 2026)
This study aims to explore the uniqueness of 16th-century Reformed Christology and its contribution to the development of contemporary church theology. The background of this study arises from concerns about efforts to reconstruct Christological dogmas that are considered no longer relevant because they are too influenced by a rigid, elitist Western metaphysical framework and do not touch on the context of the real lives of the congregation. Amidst the demands of the modern era that prioritize authentic, inclusive, and contextual experiences of faith, a merely speculative and abstract understanding of Christology becomes less functional for church life. Through a qualitative approach using historical-theological methods, this study finds that Reformed Christology emphasizes the supremacy and finality of Christ in history, as well as its relevance to the salvation of believers. The thought of reformers such as Martin Luther and John Calvin consistently places Christ at the center of faith; not merely as an object of theological contemplation, but as a living Person present in the word, sacraments, and the life of the congregation. Amid the decline in Christological understanding in the modern era, Reformed Christological thought is a theological treasure that can bridge the gap between the proclamation of the Gospel and the realities of the lives of today's congregations. The results of this study are expected to provide a real contribution in formulating a Christology that is relevant, contextual, and remains faithful to the testimony of the Bible for the Protestant church today.